USE THE ULTRACISION SCALPEL FOR DISSECTION STOMACH IN THE EXPERIMENTS - Khvorostov, E.D.; Tomin, M.S.; Sorokina, I.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The experience of experimental application apparatus methods of tissue dissection and coagulation with electrocoagulators and Harmonic Scalpel is represented. On the basis of data obtained it is determinate the peculiarities of influence on biological tissues by difficult kinds of energy and their influence on the reparatory process. The results obtained allowed us to determine positive points of applications of ultrasonic dissection and coagulation over electrosurgical instruments and recommend for gastroenteroanastomosis in the clinical practice.